2136. Development of Recombinant Rotavirus Vaccine Carrying Herpes Simplex Virus 2 Gene Based on Reverse Genetics Technology. (15th December 2022) - Kawamura, Yoshiki; Komoto, Satoshi; Fukuda, Saori; Kugita, Masanori; Tang, Shuang; Pieknik, Julianna; Enya, Yasuko; Ihira, Masaru; Nagao, Shizuko; Krause, Philip; Taniguchi, Koki; Yoshikawa, Tetsushi
Abstract: Background: Herpes simplex virus type 2 (HSV-2) can cause genital herpes, which reduces the patient's QOL associated with pain. In addition, genital herpes can increase the risk of human immunodeficiency virus infection. Vaccine development has been attempted for many years, but it has not yet been put into practical use. Meanwhile, rotavirus (RV) is one of the major viral causes of severe gastroenteritis in infants and young children worldwide. Currently, two live attenuated vaccines are widely used to prevent severe RV infection in children. We have developed entirely plasmid-based reverse genetics systems of RV, which allowed the generation of recombinant reassortant RV containing a foreign gene. In this study, we sought to develop simian RV (SA11), in which HSV-2 glycoprotein D (gD2) gene was inserted by reverse genetics system, as a herpes vaccine, and evaluated its immunogenicity in mice. Construction of HSV-2 protein expressing rotavirus as a vaccine inducing mucosal immunity Methods: Artificially synthesized gD2 DNA fragment was inserted into T7 expression NSP1 plasmids (pT7/NSP1-gD2). Using the plasmid, recombinant SA11-gD2 virus (rSA11-gD2) was generated. gD2 protein expression in infected MA104 cells was verified by Western blotting. rSA11-gD2 was orally inoculated into BALB/c suckling mice twice two weeks apart and into eight-week-old mice three times apart four weeks. Diarrhea score was evaluated for seven days after first inoculation in suckling mice. Serum IgG and IgA titers against RV and gD2 were measured by ELISA. Results: Insertion of the gD2 gene and synthesis of gD2 protein were demonstrated by sequence analysis and Wester blotting analysis, respectively. Diarrhea occurred after the first inoculation of rSA11-gD2 in suckling mice. Although IgG and IgA antibodies against RV were induced, gD2 antibody was not detected in convalescent sera in the suckling mice. Meanwhile, in the eight-week-old mice inoculated with three times of rSA11-gD2, significant increases in not only IgG and IgA against RV but also IgG against gD2 were demonstrated. Conclusion: Simian RV containing gD2 gene, which was developed by the reverse genetics, induced IgG antibody against gD2 in orally inoculated mice. This strategy can be used to develop genital herpes vaccine. Disclosures: All Authors : No reported disclosures.